Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 1766 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Patella ulyssiponensis Gmelin, 1791", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 1766 records from 34 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006436-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences